Design and engineering genetic tools for Desulfovibrio alaskensis - Cueva, Miguel Eugenio (The University of Edinburgh, 2020)
Microorganisms, such as the anaerobic bacterium Desulfovibrio alaskensis, have evolved various mechanisms to resist high concentrations of toxic heavy metals; one of these mechanisms involves the synthesis of nanoparticles (NPs). It may be possible to utilise this ability to both reclaim heavy metals from contaminated effluents and to convert them into industrially useful NPs. By engineering a genetically modified D. alaskensis, through synthetic biology, cell surface engineering and by designing a modular cloning (MoClo) toolkit, there is a further opportunity to tailor nanoparticle synthesis. DNA assembly techniques have revolutionised biotechnology research and innovation. However, despite many advances in molecular biology, the assembly of DNA parts into new constructs remains cumbersome and unpredictable. The innovation of cloning toolkits and standards such as MoClo have standardised the process of DNA assembly, making it easier, faster, modular and cost-effective. The D. alaskensis MoClo toolkit developed in this work consists of characterised oxygen-independent reporters, synthetic promoters and ribosome binding site (RBS) libraries. The D. alaskensis MoClo toolkit was utilised to assemble a combinatorial library of transcriptional units (TUs) expressing the NiFe hydrogenase small subunit. Platinum NPs were synthesised by the combinatorial library, and examined for their oxidative and reduction catalytic activities were tested. To enhance D. alaskensis resistance to Cu, Pt and Pd, cell surface engineering was used to express synthetic phytochelatin EC20 on the outer membrane. Tests of Escherichia coli expressing EC20/IgA to Cu, Pt and Pd concluded that EC20 confers a higher resistance to all metals.
Keywords: Desulfovibrio alaskensis; nanoparticles; modular cloning; MoClo toolkit; oxygen-independent reporters; synthetic promoters; ribosome binding site libraries